STRATIFIKASI PETANI SAWIT DI DESA BATANG BATINDIH KECAMATAN RUMBIO JAYA KABUPATEN KAMPAR - Rio, Malvandy Alfaulus Rizki; Bahri, Syamsul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This is done in Batang Batindih Village, Rumbio Jaya Sub-District, Kampar District. The purpose of this research is to know the formation of Farmer Class structure in Batang Batindih Village, Rumbio Jaya Sub-district, Kampar Regency. The focus of this research is the formation of the class structure created by the farmers, which is related to Farmers, Peron, Tauke, Koprasi Unit Desa (KUD), the determination of social class structure that occurs in see through the distribution pattern and also the influence of the distribution group. The technique of determining samples by Pusposive Sampling and emphasizing the number of dample as many as 9 people. The writer uses qualitative descriptive method which is done to find there are some Characteristic of Farmer, Peron, Tauke And Oil Palm Harvest Worker, Worker of loading and unloading of Peron, Oil Palm Loader of TPH field located in Batang Bihddih Village, farmers have great strength and influence in karenan has a palm oil area in the oil palm plantation in Batang Batindih Village has three oil palm distribution structures, ie Farmers - Koprasi Unit desa (KUD) - Factory, Farmer - Tauke - Peron - Factory, Farmer - Peron - Factory. The pattern of the structure will affect the group of land owners and also the distribution group, Labor. The researcher also finds the managers of palm oil distribution in providing services to Palm Oil Farmers, Labor in order to keep working together to make the distribution of distribution, Farmers and Workers profits, and to make good communication between Farmers, Laborers and managers of oil palm fisherieKeywords: Stratifikasi. Petani Sawit, Peron, Tauke, Koprasi Unit Desa (KUD)